Web Mapping on Land Cover Change of Kathmandu, Lalitpur and Bhaktapur District - Ghimire, Raj; Dhakal, Sandesh; Sapkota, Mira; KC, Yogesh; Shrestha, Reshma (Journal on Geoinformatics, Nepal, 2022)
Land cover change is rapidly following path of environmental degradation, imbalance on ecosystem. Kathmandu, Lalitpur and Bhaktapur district has experienced a very high trend of urbanization and land use land cover change. Mapping this trend is absolutely necessary for sustainable development as well as conservation of the ecosystem. While there are desktop applications for making this mapping and analysis possible, upgrading to the web is the best possible way in order to interact with public as well as much easier way of data visualization, data analysis and data dissemination. This paper portrays the design and implementation process along with the visualization of a WebGIS platform via thin client architecture. A dynamic web map portal has been developed concerning the land cover change of Kathmandu, Lalitpur and Bhaktapur district. Among the several Free Open Source server software, OpenGeo Suite has been adopted for the project because it has a robust and flexible design that allows us to reliably handle and publish geospatial data. PostgreSQL/PostGIS, QGIS, Geoserver, Leaflet, and Apache Tomcat has been utilized as the web server in this suite. A fully functional website has been developed in order to host the maps and its components. WMS layers has also been published using Geoserver and styled as can be displayed on the web map portal. Leaflet plugins has been used with the help of which different tools like Zoom, Pan, Full Screen View and Distance Calculator are made available on the portal.